Carbetocin versus oxytocin in the prevention of postpartum hemorrhage in cesarean section: a prospective randomised comparative study - Munazira, Farah; Rahman, Zarin; Ahmed, Naaz; Lal, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum hemorrhage is the leading cause of maternal mortality. The prevention of PPH can be best done by active management of the third stage of labour. Oxytocin is currently the uterotonic of choice. The study compared the efficacy of Carbetocin 100 µg intravenous bolus and oxytocin 10 IU intravenous infusion over 2 hours by measuring total blood loss, the need for additional uterotonic agents, and the need for blood transfusion. It is important to evaluate the efficacy of Carbetocin compared to oxytocin in low-income countries, especially where patient affordability is a major concern. Methods: A prospective randomised comparative single-blinded study was conducted in the department of obstetrics and gynecology, Kurji Holy Family Hospital, Patna, Bihar. 100 patients undergoing elective cesarean section fitting in the inclusion criteria were randomly allocated by a sealed envelope system to either case study group A receiving Carbetocin 100 µg intravenous and control study group B receiving oxytocin 10 IU intravenous infusion. Three specific outcomes were measured: total blood loss, additional uterotonic use and the need for blood transfusion. Results: In this study, Carbetocin was found to significantly reduce total blood loss in comparison to oxytocin (p<0.0001), the use of additional uterotonics was significantly less in the Carbetocin group (p=0.023), the need for blood transfusion was less in Carbetocin group but not significantly (p=0.538). Conclusions: Carbetocin has better efficacy in comparison to oxytocin in reducing total blood loss, hence preventing PPH. The need for additional uterotonic agents is less with Carbetocin use. The need for blood transfusion was also less with Carbetocin use but needs larger studies to be proved. Carbetocin may be cost-effective.